Exploring Relationship between Social Media Use and Antisocial Behaviour among Tertiary Institution Students: An Investigative Study of Influencing Factors (2023)
This study explored the relationship between social media use, antisocial behaviour and its impact on tertiary institution students. The influencing factors were examined. The prevalent types of antisocial behaviour on social media platforms among students in tertiary institutions, contributory factors to the development of antisocial behaviour, the average hours spent by students on social media per day, as well as the difference between male and female students in their use of social media to facilitate online harassment in tertiary institutions were identified.